A Study on Security of IP Cameras and Its Awareness - Motowidlo, Adam; Adatsi, Timothy; Jackson, Alvin; Zhao, Shushan (Indian Journal of Computer Science, 2022)
IP/smart cameras or Internet of Things (IoT) have become a popular trend over the years thanks to their many capabilities. They can automate, make tasks more manageable and monitor your home efficiently, and at the same time, make you feel safer. However, because these devices can connect to the internet, there is a possibility that they can become a security risk to the users. Whenever a smart device is accessible on the internet, it is possible for other individuals, or hackers to access the device. This research aims to identify and analyze consumers’ basic knowledge about network security and the dangers of unsecured IP cameras. The research comprises of a survey on security awareness on these devices, and experiments on exploitation of known vulnerabilities. With the results, we can understand and learn major issues about security of these devices.